Toward Energy Savings in Campus Buildings Under a Life Cycle Thinking Approach - Abejon-Elias, R (Multidisciplinary Digital Publishing Institute (MDPI), 2020)
Recent studies have identified that buildings all over the world are great contributors to energy consumption and greenhouse gas emissions. The relationship between the building industry and environmental pollution is continuously discussed. The building industry includes many phases: extraction of raw materials, manufacturing, construction, use, and demolition. Each phase consumes a large amount of energy, and subsequent emissions are released. The life cycle energy assessment (LCEA) is a simplified version of the life cycle assessment (LCA) that focuses only on the evaluation of energy inputs for different phases of the life cycle. Operational energy is the energy required for day-to-day operation processes of buildings, such as heating, cooling and ventilation systems, lighting, as well as appliances. This use phase accounts for the largest portion of energy consumption of the life cycle of conventional buildings. In addition, energy performance certification of buildings is an obligation under current European legislation, which promotes efficient energy use, so it is necessary to ensure that the energy performance of the building is upgraded to meet minimum requirements. For this purpose, this work proposes the consideration of the energy impacts and material resources used in the operation phase of a building to calculate the contribution of these energy impacts as new variables for the energy performance certification. The application of this new approach to the evaluation of university buildings has been selected as a case study. From a methodological point of view, the approach relied on the energy consumption records obtained from energy and materials audit exercises with the aid of LCA databases. Taking into practice the proposed methodology, the primary energy impact and the related emissions were assessed to simplify the decision-making process for the energy certification of buildings. From the results obtained, it was concluded that the consumption of water and other consumable items (paper) are important from energy and environmental perspectives. © 2020 by the authors. Licensee MDPI, Basel, Switzerland.